Nanomaterial modified fusion bonded epoxy resin and its properties - LIU Fuxin; DU Juan (Journal of Aeronautical Materials)
Nanomaterials can greatly improve the mechanical properties and corrosion resistance of epoxy resin, and the use of nanomaterials to modify epoxy resin is an important research direction in the field of coatings. Fusible bonded epoxy resin (FBE) was modified by ZSM-5 molecular sieve, reduced graphene oxide (rGO) and their interaction (ZSM-5-rGO). The effects of FBE on microhardness, adhesion and corrosion resistance were studied. The results show that the microhardness of ZSM-5 modified fused epoxy resin is increased by 44%. The microhardness value of rGO modified fused epoxy resin is increased by 25.7%, and its corrosion resistance is improved from 6421 Ω·cm2 to 75371 Ω·cm2. ZSM-5-rGO modified fused bonded epoxy resin has good corrosion resistance and improves the binding force with aluminum alloy matrix by nearly two times. When the ratio of ZSM-5 to rGO is 2∶1, the comprehensive modification effect of ZSM-5 on fusion bonded epoxy resin is the best, the microhardness is 38.84, and the binding force with aluminum alloy matrix is 67.5 N.